2003
DOI: 10.1093/bja/aeg107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cerebral hypoperfusion with bispectral index during paediatric cardiac surgery

Abstract: Our findings suggest that an acute decrease in BIS during acute hypotension indicates cerebral hypoperfusion, and that cerebral hypoperfusion caused by hypotension may occur frequently during paediatric cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 11 publications
1
55
0
4
Order By: Relevance
“…However, probably due to the complexity of electrode placement and interpretation, there have been very few case reports [3,4] or human studies [5] on the relationship between EEG and the state of cerebral perfusion in anaesthetised patients. BIS, derived from multivariate analysis of rolling .............................................................................................................................................................................................................. [6], decreases in its value during hypotension or cardiac arrest [1,7], analogous to the EEG changes above, have been reported. It has also been advocated as an anaesthesia monitor in cardiac surgery [8], where neurological complications are of concern, a fact that further increases the appreciation of this relationship due to the higher risk of cardiovascular complications in this type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, probably due to the complexity of electrode placement and interpretation, there have been very few case reports [3,4] or human studies [5] on the relationship between EEG and the state of cerebral perfusion in anaesthetised patients. BIS, derived from multivariate analysis of rolling .............................................................................................................................................................................................................. [6], decreases in its value during hypotension or cardiac arrest [1,7], analogous to the EEG changes above, have been reported. It has also been advocated as an anaesthesia monitor in cardiac surgery [8], where neurological complications are of concern, a fact that further increases the appreciation of this relationship due to the higher risk of cardiovascular complications in this type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashida et al 11 observed acute EEG slowing and BIS reduction in a patient at the start of cardiopulmonary bypass. They attributed the observation to cerebral hypoperfusion due to reduced arterial pressure and hemodilution.…”
Section: Discussionmentioning
confidence: 98%
“…A study done in children undergoing CPB documented the drop in BiS value at onset of CPB, though this study correlated all episodes of cerebral hypoperfusion and concluded that reduction in BiS value correlated with cerebral hypoperfusion [5]. Thomas et al [6] studied BiS in patients undergoing off pump coronary artery surgery (OPCAB) and found that the incidence of hypotension correlated with low values of BiS and proposed that BiS might be used as an indicator of cerebral hypoperfusion in OPCAB.…”
Section: Discussionmentioning
confidence: 99%